2005
DOI: 10.1113/jphysiol.2005.091801
|View full text |Cite
|
Sign up to set email alerts
|

Sodium pump α2 subunits control myogenic tone and blood pressure in mice

Abstract: A key question in hypertension is: How is long-term blood pressure controlled? A clue is that chronic salt retention elevates an endogenous ouabain-like compound (EOLC) and induces salt-dependent hypertension mediated by Na + /Ca 2+ exchange (NCX). The precise mechanism, however, is unresolved. Here we study blood pressure and isolated small arteries of mice with reduced expression of Na + pump α1 (α1 +/-) or α2 (α2 +/-) catalytic subunits. Both low-dose ouabain (1-100 nM; inhibits only α2) and high-dose ouaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
255
4
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(280 citation statements)
references
References 63 publications
14
255
4
7
Order By: Relevance
“…of three independent experiments are shown P2Y 13 ) have been cloned from mammalian cDNA libraries [14]. Among them, P2X 1 , P2X 2 , P2X 4 , P2X 5 , P2Y 2 , P2Y 4 , and P2Y 6 mRNA species and proteins interacting with anti-P2X 1 , anti-P2Y 2 , and anti-P2Y 6 antibodies have been detected in rodent small arteries [36][37][38][39][40]. Our results show that transient and sustained constrictions of mouse mesenteric arteries evoked by ATP and UTP, respectively, are mainly mediated by P2X 1 and P2Y 6 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…of three independent experiments are shown P2Y 13 ) have been cloned from mammalian cDNA libraries [14]. Among them, P2X 1 , P2X 2 , P2X 4 , P2X 5 , P2Y 2 , P2Y 4 , and P2Y 6 mRNA species and proteins interacting with anti-P2X 1 , anti-P2Y 2 , and anti-P2Y 6 antibodies have been detected in rodent small arteries [36][37][38][39][40]. Our results show that transient and sustained constrictions of mouse mesenteric arteries evoked by ATP and UTP, respectively, are mainly mediated by P2X 1 and P2Y 6 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This response was unaffected by ␣-adrenergic blockade and, thus, was not due to catechomaine release from sympathetic neurons in the artery wall. The effect of ouabain also was maintained following endothelium removal (120). The half-maximally effective concentration of ouabain (EC 50 ) was 1.3 nM (120).…”
Section: How Does Low-dose Ouabain Augment Contractility?mentioning
confidence: 94%
“…The compound appears as a novel drug that may also target these altered molecular mechanisms in patients. Indeed, previous findings have indicated that rostafuroxin is a potent and safe drug (Ferrari et al, 1999a,b) able to counteract hypertension development, and the related hypertensive effects, induced by mutant a-adducin and ouabain at renal and vascular levels, preventing cardiac and renal hypertrophy in the long run in animal models Zhang et al, 2005). More recently, a pharmacologic clinical trial has shown that rostafuroxin also normalizes BP levels in patients carrying a selective genetic profile that includes genes encoding for adducin variants and enzymes controlling ouabain synthesis and transport (Lanzani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%